(untitled) (Social Science Review, 2025)
The regional diversity in civil service may foster more equitable distribution of public resources and an increase in innovative service delivery. Before 2018, the government of Bangladesh relied on the districts’ share of population as a tool to ensure regional variation in the civil service. There is no systematic research in the existing literature exploring the effects of different types of quotas on the representativeness of bureaucracy in Bangladesh. In this study, we attempt to address this gap in the literature and explore to what extent the population share based quota system contributes to improving the representation of underserved regions of the country. It is found that the districts’ share of population and share of freedom fighters play a major role in determining the regional representativeness in the BCS administration cadre. Among the socio-economic factors, university completion rates of the districts are found to be positively correlated with the districts’ share of officials, while the sign of the coefficient on the poverty rates of the districts changes from positive to negative. Social Science Review, Vol. 41(1), June 2024, Page 237-259.